2018
DOI: 10.33772/jitro.v3i2.1679
|View full text |Cite
|
Sign up to set email alerts
|

Kajian Pertumbuhan Karkas Dan Bagian Non Karkas Kambing Lokal Jantan Pasca Pemberian Asam Lemak Terproteksi

Abstract: Tujuan penelitian untuk mengkaji produksi karkas, non karkas, edible portion dan non edible portion dari non  karkas kambing lokal lepas sapih yang diberi asam lemak terproteksi. Materi penelitian terdiri dari kambing jantan lokal umur 4-6 bulan sebanyak 16 ekor dengan kisaran bobot badan 10-12 kg, pakan hijauan dan ALT.  Pakan yang digunakan terdiri dari hijauan dan campuran asam lemak terproteksi.  Rancangan penelitian adalah rancangan  acak  lengkap (RAL) dengan 4 perlakuan dan 4 ulangan, dengan perlakuan P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
0
4
1
Order By: Relevance
“…The difference in slaughter weight was probably due to almost the same feed quality: the protein and energy concentrates given by corn, respectively, 14.54% and 68.38% and bread waste, 14.40% and 66.57%. The slaughter weight results in this study were lower when compared with research by Elvanuddin et al (2018), in which the slaughter weight of Kacang goats ranged from 14.96-20.95 kg. The study's results reported by Khotijah et al (2019) showed that the slaughter weight of male Kacang goats was 19.17-19.68 kg.…”
Section: Carcass and Non-carcass Weightcontrasting
confidence: 89%
“…The difference in slaughter weight was probably due to almost the same feed quality: the protein and energy concentrates given by corn, respectively, 14.54% and 68.38% and bread waste, 14.40% and 66.57%. The slaughter weight results in this study were lower when compared with research by Elvanuddin et al (2018), in which the slaughter weight of Kacang goats ranged from 14.96-20.95 kg. The study's results reported by Khotijah et al (2019) showed that the slaughter weight of male Kacang goats was 19.17-19.68 kg.…”
Section: Carcass and Non-carcass Weightcontrasting
confidence: 89%
“…The components of feed used by livestock are called nutrients. Feed serves as the development and maintenance of the body, a source of energy, production, and regulator of processes in the body (Elvanuddin et al, 2018). Feeding time has a very significant effect on body weight gain and the efficiency of using goat feed (Nuriadin et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…The same results were shown in the addition of simvastatin (C4), which did not result in a significant increase in kidney weight. According to Elvannudin et al (2016), the average kidney weight decreased, indicating that the last detoxification activity in the body was reduced.…”
Section: Resultsmentioning
confidence: 99%